The Effect of Transformational Leadership on Administrative Empowerment: A Field Study at Pharmaceutical Manufacturers in Yemen - Prof. Dr. Abdullatif Musleh Mohammed Ayedh; Dr. Abdulkarem Saleh Hussein Al-Qahfa (مجلة الدراسات الاجتماعية, 2020)
The study aimed to measure the impact of transformational leadership on administrative empowerment, and identify the level of practicing it at pharmaceutical manufacturers in Yemen. It also aimed to identify the level of administrative empowerment practice in these companies. To achieve the objectives of the study, the descriptive and analytical method was adopted, and a questionnaire was distributed to a sample of 330 participants selected by the complete sensus sampling method. However, only 227 of the questionnaires were valid for analysis. For data analysis, many descriptive and inferential statistical methods were used. Findings revealed that the level of practicing transformational leadership did not reach the expected level, as the mean was just medium. There were differences at the level of practicing the dimensions of transformational leadership; the highest effective difference was the intellectual arousal and the least one was the individualized consideration. Findings also showed that the level of administrative empowerment practice was medium, and the practice level of the dimension of authority delegation was high while participation in decision-making was low. Moreover, there were differences at the level of the impact of the dimensions of transformational leadership on administrative empowerment; the highest effective difference was the ideal effect and the least one was the individualized consideration. The study stressed the need to adopt various dimensions of transformational leadership, at pharmaceutical manufacturers in Yemen, with an emphasis on individualized consideration as this can have a great impact on administrative empowerment.